Spatial Disparities in Developing Countries: Cities, Regions and International Trade. - Venables, A (Centre for Economic Performance, LSE, 2003)
Spatial inequality in developing countries is due to the natural advantages of some regionsrelative to others and to the presence of agglomeration forces, leading to clustering ofactivity. This paper reviews and develops some simple models that capture these first andsecond nature economic geographies. The presence of increasing returns to scale in citiesleads to urban structures that are not optimally sized. This depresses the return to jobcreation, possibly retarding development. Looking at the wider regional structure,development can be associated with large shifts in the location of activity as industry goesfrom being inward looking to being export oriented.